KERAGAMAN PLASMA NUTFAH TANAMAN DURIAN (DURIO ZIBETHINUS MURR) DI PULAU BANGKA: Diversity of Durian Germplasm (Durio zibethinus Murr) In Bangka Island - Mustikarini, Eries Dyah; Prayoga, Gigih Ibnu; BI, Pardana (Enviagro: Jurnal Pertanian dan Lingkungan, 2024)
Durians In Bangka island have potensials of the diversity which has not been identified yet. The protection of the genetical plants of durian resources have been done by exploration and identification activities. The aim of this research are to discover the amount of Germplasm, the relationship, and the diversity of phenotype of durians in Bangka island. This research started from December 2020 to March 2021. The determination of location has been done by purposive sampling and the technique of taking samples also has been done by convenience sampling. Germplasm characterization consists of qualitative and quantitative characters. The analysis of relationships were used by dendogram according to UPGMA method. The results have discovered over 14 germplasm of durian in Bangka island. Those are Belo,Bujang Kuning, Mangga, Rudal, Katon, Sihijua, Sibola Emas, Putri Dewa, Petaling, Burak 1, Burak 2, Burak 3, T 9, and Simanis. The results of the relationships qualitative analysis were obtained 5 clusters in the level of coefficient similarities 0.49 or 49%. Meanwhile, quantitative were obtained 7 clusters in the level of coefficient 0.31 or 31% and the combined were obtained 5 clusters in the level of coefficient 0.45 or 45%.